HACKING THE TRACKS OF ANTI-SCIENCE GROUPS DURING THE COVID-19 PANDEMIC - Thaufiq Hidayat; Elfi Tajuddin; Vici Ramananda; Asmawati Asmawati (JURNAL AL-AQIDAH, 2022)
The presence of covid-19 has been over 2 years, but it is still a problem in understanding and attitude. There are still those who tend to reject the existence of Covid-19. The author considers this phenomenon an antiscience attitude whose impact can hinder handling the covid-19 outbreak. Therefore, it is important for all parties, especially the government, to intervene to deal with groups with antiscience labels. This paper only highlights how the figures and characters of antiscience groups and the impact of the pandemic era. This study aims to reveal the theoretical identity of the antiscience group in dealing with the covid-19 virus. The researcher uses a qualitative approach (library study) by studying documents related to the problems discussed in the research process. Researchers apply the description method in describing the problem as a whole and interpretive analysis to conclude. The results of this study are that the representation of the group in this paper the authors make tends to conflict with religion and science, use religious arguments for personal gain, have a very excessive belief orientation, and use ego rather than reason. The attitude of this group will have an impact on several possibilities, such as making it easier for someone to contract the coronavirus, hampering government efforts in handling covid, causing anxiety for others, and accelerating the growth rate of this virus.